Nitrogen-Induced Suicidal Asphyxiation In Maharashtra State Of India- A Case Report (Journal of Forensic Medicine & Toxicology, 2026)
Suicidal death by nitrogen-induced asphyxiation is not uncommon worldwide other than India. Seldom incidents of this  phenomenon occurred in India in recent years which is an unusual suicide method among Indians. This article presents a  case report of nitrogen-induced suicidal asphyxiation from Maharashtra State in India. A young male committed suicide  by placing a black plastic bag over the head and using commercial nitrogengas cylinder.In this case, a forensic autopsy  was carried out including toxicological analysis. Apart from signs of asphyxia, autopsy didn’t reveal any positive finding.  Toxicological analysis revealed no findings contributing to the deaths. The absence of toxicological and autopsy findings  to determine the cause of death in such cases may represent challenges of clinical and forensic significance.
Keywords: Nitrogen suicide; asphyxiation; inert gas